COPYRIGHT ISSUE IN ARTIFICIAL INTELLIGENCE APPLICATIONS OF SMART PRODUCTION AND AUTONOMOUS SYSTEMS - Alparslan, Gulde (PEOPLE: International Journal of Social Sciences, 2024)
Background: In recent years, the use of artificial intelligence in the field of production and design has increased. As a result, in smart production and autonomous systems, the concepts of copyright and rights ownership on the works produced have become increasingly complex. In addition, there is no sufficient legal regulation regarding the rights of the software side of the system, the content providers and the commercial parties with whom they have agreements, in the productions made by autonomous systems through artificial intelligence software. In addition to the ownership of the work, the copyright of the elements in the content of the work and those who produce these elements also emerge as an important problem in productions made with artificial intelligence. Purpose of Study: In this study, it is aimed to examine the copyright issue in artificial intelligence applications of smart production and autonomous systems. Sources of Evidence: In the research, a literature review was conducted and semiotic analysis and content analysis were conducted based on academic studies. According to the results obtained, analyzes were made regarding the deficiencies in copyright and the main problems arising from field applications in smart production and autonomous systems made through artificial intelligence. Main Argument: The main argument of the research is that copyright is an important problem in both the short and long term in smart production and autonomous systems produced through artificial intelligence. Conclusions: Although DSM Directive 2019/790/EU, which was issued in 2016 and came into force in 2019, regulates digital copyrights, there are serious deficiencies regarding the ownership of the system or work and the legal regulations regarding smart productions and autonomous systems produced through artificial intelligence. While DSM Directive 2019/790/EU targets a uniform digital market, the copyright issue in artificial intelligence applications shows that this regulation is also inadequate. Regarding the AI Act, there is not yet sufficient regulation or implementation data regarding copyrights. The United States Copyright Office published in 2023 points out similar deficiencies in artificial intelligence and copyrights. Existing copyright regulations are insufficient today, especially for smart products produced by autonomous systems. One of the most important sources of the problem is that the work, its ownership, the types of work, and the commercial and moral values of the work are not fully defined. For a solution, comprehensive and advanced studies are needed regarding the copyrights of artificial intelligence.